Anatomical Considerations for the Development of a New Transcatheter Aortopulmonary Shunt Device in Patients with Severe Pulmonary Arterial Hypertension. (1st September 2013) - Guo, Kenneth; Langleben, David; Afilalo, Jonathan; Shimony, Avi; Leask, Richard; Marelli, Ariane; Martucci, Giuseppe; Therrien, Judith
Abstract : Morbidity from pulmonary arterial hypertension (PAH) ensues when the pulmonary pressure reaches suprasystemic levels. A transcatheter alternative to the Potts shunt would allow decompression of the right heart without the surgical risks. To aid development of a transcatheter aortopulmonary shunt (TAPS) device, we described the anatomic relationship between the left pulmonary artery (LPA) and the descending aorta (dAO) in adults with severe pulmonary hypertension. Adults with severe PAH (peak systolic pulmonary arterial pressure [PASP] ≥80 mmHg) who had computed tomography of the chest were enrolled. Measurements were taken on the axial plane at the level of the pulmonary artery bifurcation. Forty patients (male sex, 9 patients; median age ± standard deviation [SD], 59 ± 15 years; median PASP ± SD, 93 ± 12 mmHg) were identified. The mean distance (±SD) between the LPA and dAO was 2.3 ± 3.1 mm. The mean luminal dAO and LPA diameters (±SD) were 23.4 ± 3.8 mm and 25.5 ± 5.1 mm, respectively. The LPA and dAO approximated in 93% of patients, with 38% having aortic calcification at the contact site. The mean "landing zone" width and height (defining an area with distance <4 mm between the outer borders) of the two arteries were 15.7 ± 3.4 mm and 20.6 ± 4.3 mm, respectively, at a mean distance of 28.0 ± 7.6 mm from the main pulmonary artery bifurcation. This study shows that the landing zone is able to accommodate a TAPS device of up to 15 mm in diameter in the majority of patients with severe PAH.